Strategic cooperation of Ukrainian industrial enterprises to create competitive advantages in the world market - ZRYBNIEVA, IRYNA (International Journal of Criminology and Sociology, 2020)
Competitive advantages in the market can be accumulated both with the use of the mechanism of cooperation, and as a result of coordination in the interregional sphere. The relevance of the study is determined primarily by the fact that cooperation between organisations allows to increase competitiveness in the foreign market. However, this gives rise to a contradiction that determines that cooperation between companies is possible only if the conglomerate or certain entities own controlling shares. With that, companies should not only constitute holding structures, but primarily be co-operators in the production cycle. The novelty of the study is determined by the fact that strategic cooperation is proposed to be considered not only as a set of practical actions on the part of the state or regulatory structures, but also of consulting bodies. It is proposed to use the mechanisms of strategic cooperation based on mutual conditionality of interests and security of budgetary mechanisms that allow for practical activities. The authors also admit the possibility of the use of public-private partnership mechanisms. The practical significance of the study is determined by the fact that each of the participants in the organisation of strategic management of enterprises can use not only strategic, but financial and systemic interaction mechanisms to form.
Keywords: Local government system; agricultural development; sectoral structure; strategy formation; resource provision